Preparation method and application of zinc-air battery difunctional electrocatalyst

By using boron-doped graphite carbon-encapsulated CoFe alloy in zinc air battery catalyst, the problem of easy corrosion and insufficient stability of the catalyst in alkaline environment is solved, and higher catalytic activity and cyclic stability are achieved sex.

CN119447327APending Publication Date: 2025-02-14SHANGQIU NORMAL UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411575527.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Existing zinc-air battery catalysts are prone to corrosion in alkaline environments and have insufficient stability and catalytic activity, resulting in poor energy efficiency and recycling life.

Method used

A preparation method is adopted, by synthesizing MOF precursors, cobalt salt and iron salt are added in situ, high-temperature pyrolysis is performed, and then boron source is added for secondary pyrolysis, obtaining boron-doped graphite carbon-encapsulated CoFe alloy double-site zinc Dual-function electrocatalyst for empty batteries.

Benefits of technology

The stability and catalytic activity of the catalyst are improved, the catalytic performance of OER and ORR reactions are enhanced, and the cycle life is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447327A_ABST
    Figure CN119447327A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a difunctional electrocatalyst for a zinc-air battery, cobalt salt and iron salt are added in situ while an MOF precursor is synthesized, a boron source is added after first high-temperature pyrolysis, and then a boron-doped graphite carbon-coated CoFe alloy double-site zinc-air battery difunctional electrocatalyst is obtained after second high-temperature pyrolysis. According to the pyrolyzed boron-doped graphite carbon substrate, on one hand, internal CoFe alloy double sites are protected against corrosion, and the stability performance of the catalyst is greatly improved; on the other hand, the doping of boron increases the defects of the carbon substrate, so that the catalyst exposes more active sites, and the catalytic activity of the catalyst is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of zinc-air battery catalysts, and specifically relates to a preparation method and application of a zinc-air battery bifunctional electrocatalyst. Background Art

[0002] The growing demand for energy and the international mission to combat climate change have driven and accelerated the transition from fossil fuels to clean renewable energy. Considering the limited fossil fuel resources on Earth and the rapidly deteriorating global environment, the global demand for sustainable and green energy storage technologies is increasing dramatically in order to achieve the "dual carbon goals". Therefore, the demand for sustainable green energy systems is also growing around the world, stimulating people's interest in battery technologies with high energy density, high safety and economy, and stimulating great efforts in the development and improvement of new energy storage and conversion technologies.

[0003] Zinc-air batteries have been widely studied due to their high theoretical energy density and environmental friendliness. However, the energy efficiency and cycle life of this new energy device are currently poor. In order to achieve high energy efficiency and recyclability, high-performance catalysts are constructed by optimizing strategies and the adaptability of alternative active materials. Similarly, new and improved catalysts need to be designed to have high catalytic activity and high cycle stability to improve the energy efficiency and cycle life of new energy devices. Efforts to design catalyst materials to increase the intrinsic activity of active sites or increase the number of active sites are effective methods to improve electrode performance.

[0004] Bimetallic alloying is a strategy for synthesizing dual-site catalysts by incorporating metals into clusters or nanoparticles to form a domain. Exogenous metals can significantly change the electronic, strain, and catalytic properties of alloys compared to single metals. In recent years, alloying transition metals has been a very effective strategy to improve the performance of catalysts. Binary metal alloy catalysts are a type of dual-site catalysts, where metals interact with each other and can effectively improve the performance of catalysts. However, most alloy-based dual-site catalysts corrode and deteriorate in alkaline environments, reducing their activity. In addition, the stability of binary alloy-based dual-site catalysts needs to be further improved. In order to avoid chemical corrosion, the alloy dual-site nanostructure is wrapped with a carbon layer, and the internal metal site has good durability due to the protection of the carbon layer. However, the external carbon layer structure has a certain degree of inhibition on the internal metal active sites, resulting in unsatisfactory catalytic activity. Therefore, it is particularly important to increase the stability of alloy dual-site nanostructure catalysts while exploring strategies that can expose sufficient active sites during the catalytic process.

[0005] Density functional theory calculations show that boron (B)-doped carbon lowers the Fermi level of carbon by creating electron defects in graphitic carbon while maintaining the planar structure of carbon, providing a broad application prospect for electrocatalysts. In addition, B is a promising dopant because it lacks electrons, with only three valence electrons, and can easily polarize the surrounding atoms, resulting in changes in the electron density of the active sites of the catalyst, improving its catalytic performance.

[0006] The literature (DOI: 10.1002 / chem.202300321) reports a nitrogen-doped carbon-coated NiCo alloy zinc-air battery catalyst. The catalyst uses NiCo coordination compound as a precursor and synthesizes nitrogen-doped carbon-coated NiCo alloy (NiCo@NC) through an in-situ calcination strategy. This method involves an in-situ calcination strategy, but does not involve a secondary calcination process, and the cyclic stability of the catalyst prepared by this method still needs to be further improved. Summary of the invention

[0007] The technical problem solved by the present invention is to provide a preparation method and application of a zinc-air battery bifunctional electrocatalyst. The zinc-air battery bifunctional electrocatalyst prepared by the method is used for OER and ORR reactions of the zinc-air battery, effectively improving the performance of the zinc-air battery.

[0008] The present invention adopts the following technical scheme to solve the above technical problems, a method for preparing a zinc-air battery bifunctional electrocatalyst, characterized in that the specific process is as follows: the zinc-air battery bifunctional electrocatalyst is prepared by adding cobalt salt and iron salt in situ while synthesizing the MOF precursor, adding a boron source after the first high-temperature pyrolysis, and then performing a second high-temperature pyrolysis to obtain a boron-doped graphite carbon-wrapped CoFe alloy bi-site zinc-air battery bifunctional electrocatalyst. The boron-doped graphite carbon substrate after pyrolysis, on the one hand, protects the internal CoFe alloy bi-site from corrosion, greatly improving the stability of the catalyst; on the other hand, the boron doping increases the defects of the carbon substrate, so that the catalyst exposes more active sites, effectively improving the catalytic activity of the catalyst.

[0009] A method for preparing a zinc-air battery bifunctional electrocatalyst, characterized in that the specific process is: Step S1, while synthesizing the MOF precursor, cobalt salt and iron salt are added in situ, and then pyrolyzed at 900-1000° C. to obtain the intermediate product CoFe-NC, wherein the cobalt salt is one or more of cobalt nitrate, cobalt chloride or cobalt acetate, and the iron salt is one or more of iron nitrate, iron chloride or iron sulfate; Step S2, the intermediate product CoFe-NC obtained in step S1 and the boron source are evenly mixed and then pyrolyzed at a high temperature of 900-1000°C to obtain a boron-doped graphite carbon-wrapped CoFe alloy dual-site zinc-air battery bifunctional electrocatalyst, wherein the boron source is one or more of boric acid or sodium borate.

[0010] A method for preparing a bifunctional electrocatalyst for a zinc-air battery, characterized in that the specific steps are: Step S1, dissolving 2g zinc nitrate, 50-100mg cobalt salt and 500-1000mg iron salt in 80mL methanol solution to obtain solution A, dissolving 6g 2-methylimidazole in 80mL methanol solution to obtain solution B, mixing solution A and solution B evenly and standing at room temperature for 12h, washing with ethanol by centrifugation several times and then vacuum drying to obtain a precursor CoFe-MOF; Step S2, performing a first high-temperature pyrolysis of the precursor CoFe-MOF in a high-purity argon atmosphere to obtain an intermediate product CoFe-NC, wherein the pyrolysis temperature is 950° C., the heating rate is 10° C. / min, and the pyrolysis time is 3 h; Step S3, dispersing the intermediate product CoFe-NC and the boron source in water, stirring and reacting at 60° C. for 8 to 10 hours, washing with water once for 4 times after the reaction, and vacuum drying to obtain the boron-containing intermediate product CoFe-NC-B; Step S4, subjecting the boron-containing intermediate product CoFe-NC-B to a second high-temperature pyrolysis to obtain a boron-doped graphite carbon-wrapped CoFe alloy dual-site zinc-air battery bifunctional electrocatalyst CoFe-NBC, wherein the pyrolysis temperature is 950°C, the heating rate is 10°C / min, and the pyrolysis time is 3h.

[0011] Further preferably, in step S3, the mass ratio of the intermediate product CoFe-NC to the boron source is 1:0.5~1.

[0012] The invention discloses an application of the zinc-air battery bifunctional electrocatalyst in the preparation of a zinc-air battery. When the zinc-air battery bifunctional electrocatalyst catalyzes the half-reactions OER and ORR of the zinc-air battery, the active ingredient CoFe alloy dual site plays a major catalytic role. Due to the introduction of heteroatom boron, not only the electronic structure of the active site CoFe alloy is changed, thereby improving the electrocatalytic performance of the catalyst, but also the boron doping changes the structure of the external carbon layer, thereby exposing more active sites of the catalyst, thereby increasing the contact area between the catalyst and the electrolyte and giving full play to the role of the active sites of the catalyst. In addition, the boron-doped carbon layer protects the internal CoFe alloy dual site from corrosion, thereby greatly improving the cycle stability of the catalyst, thereby having good OER and ORR bifunctional catalytic performance.

[0013] Compared with the prior art, the present invention has the following advantages and beneficial effects: 1. The present invention successfully synthesized a zinc-air battery bifunctional electrocatalyst with CoFe-MOF as a precursor. The pyrolysis of the precursor changed the structure of the external carbon layer, forming a structure that encapsulates the active sites, protecting the internal active sites from corrosion, and greatly improving the cyclic stability of the catalyst.

[0014] 2. The boron doping in the zinc-air battery bifunctional electrocatalyst prepared by the present invention increases the defects of the carbon layer and increases the contact between the internal active sites and the electrolyte. Therefore, the boron-doped carbon structure protects the internal active sites from corrosion while increasing the contact with the electrolyte, improving the cycle stability while maintaining its catalytic activity. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 is the XRD pattern of the sample prepared in Example 1; Figure 2 is the XRD pattern of the sample prepared in Example 2; Figure 3 ORR polarization curves of samples prepared in Example 1, Example 2 and Comparative Example 1, Comparative Example 2; Figure 4 This is an ORR stability (IT) test of the samples prepared in Example 1, Example 2 and Comparative Example 1, Comparative Example 2. DETAILED DESCRIPTION

[0016] The above contents of the present invention are further described in detail below through examples, but this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples, and all technologies implemented based on the above contents of the present invention belong to the scope of the present invention. Example 1

[0017] Step S1: 2 g of zinc nitrate, 50 mg of cobalt chloride and 500 mg of ferric nitrate were dissolved in 80 mL of methanol solution to obtain solution A, 6 g of 2-methylimidazole was dissolved in 80 mL of methanol solution to obtain solution B, solution A and solution B were mixed evenly and allowed to stand at room temperature for 12 h, washed several times by centrifugation with ethanol, and vacuum dried to obtain the precursor CoFe-MOF.

[0018] Step S2: The precursor CoFe-MOF is subjected to the first high-temperature pyrolysis in a high-purity argon atmosphere to obtain the intermediate product CoFe-NC, wherein the pyrolysis temperature is 950° C., the heating rate is 10° C. / min, and the pyrolysis time is 3 h.

[0019] Step S3: Disperse 40 mg of the intermediate product CoFe-NC and 20 mg of boric acid in 20 mL of H 2 O, stirred at 60 ° C for 9 h, and after the reaction was completed, washed with water four times and vacuum dried to obtain the boron-containing intermediate product CoFe-NC-B.

[0020] Step S4: subjecting the boron-containing intermediate product CoFe-NC-B to a second high-temperature pyrolysis to obtain a boron-doped graphite carbon-wrapped CoFe alloy dual-site zinc-air battery bifunctional electrocatalyst CoFe-NBC, wherein the pyrolysis temperature is 950°C, the heating rate is 10°C / min, and the pyrolysis time is 3h. Example 2

[0021] Step S1: 2 g of zinc nitrate, 100 mg of cobalt chloride and 1000 mg of ferric nitrate were dissolved in 80 mL of methanol solution to obtain solution A, 6 g of 2-methylimidazole was dissolved in 80 mL of methanol solution to obtain solution B, solution A and solution B were mixed evenly and allowed to stand at room temperature for 12 h, washed several times by centrifugation with ethanol, and dried in vacuo to obtain the precursor CoFe-MOF.

[0022] Step S2: The precursor CoFe-MOF is subjected to the first high-temperature pyrolysis in a high-purity argon atmosphere to obtain the intermediate product CoFe-NC, wherein the pyrolysis temperature is 950° C., the heating rate is 10° C. / min, and the pyrolysis time is 3 h.

[0023] Step S3: Disperse 40 mg of the intermediate product CoFe-NC and 20 mg of sodium borate in 20 mL of H 2 O, stirred at 60 ° C for 9 h, and after the reaction was completed, washed with water four times and vacuum dried to obtain the boron-containing intermediate product CoFe-NC-B.

[0024] Step S4: subjecting the boron-containing intermediate product CoFe-NC-B to a second high-temperature pyrolysis to obtain a boron-doped graphite carbon-wrapped CoFe alloy dual-site zinc-air battery bifunctional electrocatalyst CoFe-NBC, wherein the pyrolysis temperature is 950°C, the heating rate is 10°C / min, and the pyrolysis time is 3h.

[0025] Comparative Example 1 (without secondary pyrolysis) Step S1: 2 g of zinc nitrate, 100 mg of cobalt chloride and 1000 mg of ferric nitrate were dissolved in 80 mL of methanol solution to obtain solution A, 6 g of 2-methylimidazole was dissolved in 80 mL of methanol solution to obtain solution B, solution A and solution B were mixed evenly and allowed to stand at room temperature for 12 h, washed several times by centrifugation with ethanol, and dried in vacuo to obtain the precursor CoFe-MOF.

[0026] Step S2: The precursor CoFe-MOF is subjected to high-temperature pyrolysis in a high-purity argon atmosphere to obtain an intermediate product CoFe-NC, wherein the pyrolysis temperature is 950° C., the heating rate is 10° C. / min, and the pyrolysis time is 3 h.

[0027] Step S3: Disperse 40 mg of the intermediate product CoFe-NC and 20 mg of sodium borate in 20 mL of H 2O, stirred at 60 ° C for 9 h, and after the reaction was completed, washed with water four times and vacuum dried to obtain a boron-containing catalyst.

[0028] Comparative Example 2 (no boron doping) Step S1: 2 g of zinc nitrate, 100 mg of cobalt chloride and 1000 mg of ferric nitrate were dissolved in 80 mL of methanol solution to obtain solution A, 6 g of 2-methylimidazole was dissolved in 80 mL of methanol solution to obtain solution B, solution A and solution B were mixed evenly and allowed to stand at room temperature for 12 h, washed several times by centrifugation with ethanol, and dried in vacuo to obtain the precursor CoFe-MOF.

[0029] Step S2: The precursor CoFe-MOF is subjected to the first high-temperature pyrolysis in a high-purity argon atmosphere to obtain the intermediate product CoFe-NC, wherein the pyrolysis temperature is 950° C., the heating rate is 10° C. / min, and the pyrolysis time is 3 h.

[0030] Step S3: subjecting the intermediate product CoFe-NC to a second high-temperature pyrolysis to obtain a boron-free doped catalyst CoFe-NC, wherein the pyrolysis temperature is 950° C., the heating rate is 10° C. / min, and the pyrolysis time is 3 h.

[0031] The above embodiments describe the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for illustrating the principles of the present invention. Without departing from the scope of the principles of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of protection of the present invention.

Claims

1. A method for preparing a bifunctional electrocatalyst for a zinc-air battery, characterized in that The specific process is: Step S1, while synthesizing the MOF precursor, cobalt salt and iron salt are added in situ, and then pyrolyzed at 900-1000° C. to obtain the intermediate product CoFe-NC, wherein the cobalt salt is one or more of cobalt nitrate, cobalt chloride or cobalt acetate, and the iron salt is one or more of iron nitrate, iron chloride or iron sulfate; Step S2, the intermediate product CoFe-NC obtained in step S1 and the boron source are evenly mixed and then pyrolyzed at a high temperature of 900-1000°C to obtain a boron-doped graphite carbon-wrapped CoFe alloy dual-site zinc-air battery bifunctional electrocatalyst, wherein the boron source is one or more of boric acid or sodium borate.

2. The method for preparing the bifunctional electrocatalyst for zinc-air batteries according to claim 1, characterized in that The specific steps are: Step S1, dissolving 2g zinc nitrate, 50-100mg cobalt salt and 500-1000mg iron salt in 80mL methanol solution to obtain solution A, dissolving 6g 2-methylimidazole in 80mL methanol solution to obtain solution B, mixing solution A and solution B evenly and standing at room temperature for 12h, washing with ethanol by centrifugation several times and then vacuum drying to obtain a precursor CoFe-MOF; Step S2, performing a first high-temperature pyrolysis of the precursor CoFe-MOF in a high-purity argon atmosphere to obtain an intermediate product CoFe-NC, wherein the pyrolysis temperature is 950° C., the heating rate is 10° C. / min, and the pyrolysis time is 3 h; Step S3, dispersing the intermediate product CoFe-NC and the boron source in water, stirring and reacting at 60° C. for 8 to 10 hours, washing with water once for 4 times after the reaction, and vacuum drying to obtain the boron-containing intermediate product CoFe-NC-B; Step S4, subjecting the boron-containing intermediate product CoFe-NC-B to a second high-temperature pyrolysis to obtain a boron-doped graphite carbon-wrapped CoFe alloy dual-site zinc-air battery bifunctional electrocatalyst CoFe-NBC, wherein the pyrolysis temperature is 950°C, the heating rate is 10°C / min, and the pyrolysis time is 3h.

3. The method for preparing the bifunctional electrocatalyst for zinc-air batteries according to claim 2, characterized in that: The mass ratio of the intermediate product CoFe-NC to the boron source in step S3 is 1:0.5~1.

4. The use of a zinc-air battery bifunctional electrocatalyst prepared by the method according to any one of claims 1 to 3 in the preparation of a zinc-air battery, wherein when the zinc-air battery bifunctional electrocatalyst catalyzes the half-reactions OER and ORR of the zinc-air battery, the active ingredient CoFe alloy dual site plays a major catalytic role. Due to the introduction of heteroatom boron, not only the electronic structure of the active site CoFe alloy is changed, thereby improving the electrocatalytic performance of the catalyst, but also the boron doping changes the structure of the external carbon layer, so that the catalyst exposes more active sites, thereby increasing the contact area between the catalyst and the electrolyte, and giving full play to the role of the active sites of the catalyst. In addition, the boron-doped carbon layer protects the internal CoFe alloy dual site from corrosion, greatly improving the cycle stability of the catalyst, and thus has good OER and ORR bifunctional catalytic performance.